METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA SISWA TUNAGRAHITA - Ayuni Ayuni (Tarbiya Islamica, 2014)
The purpose of this study is to reveal about: 1) the methods used by teachers in learning Islamic Religious Education for mentally retarded students at the Sambas State Special School in 2019/2020; 2) The evaluation used by teachers in learning Islamic Religious Education for mentally retarded students at the Sambas State Special School in 2019/2020. This study uses a qualitative approach and the type of descriptive research. Data collection techniques using direct observation techniques, structured interviews, and documentation using cellphones and notebooks as collection tools. The results of the study can be concluded that: 1. The methods used in PAI learning for mentally retarded students at the Sambas State Special School are: a) the lecture method is used in the learning process; b) Demonstration method when giving examples of movement in prayer material; c) The teacher uses the question and answer method at the end of the lesson to see the students' ability to absorb the material presented. The evaluations used in PAI learning for mentally retarded students at the Sambas State Special School are: The teacher provides an evaluation of learning to mentally retarded students when students practice prayer movements, immediately provides an assessment in the form of practice.